Characterization and Prognostic Significance of Cutaneous Immune-Related Adverse Events in Indian Patients on Immune Checkpoint Inhibitor Therapy - Duraisamy, Prasanna; Panicker, Vinitha; Jose, Wesley (Dermatology Practical & Conceptual, 2023)
Introduction: Cutaneous immune-related adverse-events (cIRAEs), commonly seen in cancer patients receiving immune checkpoint inhibitors (ICI) are reported to be associated with better patient survival; however, they have seldom been studied in Indian population. Recent reports suggest racial differences in IRAEs and also in survival outcomes.Objective: To study the various cIRAEs in Indian patients on ICI therapy and to analyze the association between cIRAEs and patient survival outcomes.Methods: We conducted a retrospective cohort study of 86 cancer patients receiving immunotherapies in a tertiary care hospital in India and studied incidence, nature and grades of cutaneous immune-related adverse events and the association of cIRAEs with the patient survival outcomes.Results: Eighty-six patients were included, of whom 16 patients (18.6%) developed cIRAEs, with pruritus (12.8%) and maculopapular eruption (8.1%) being the most common. Kaplan–Meier plot with log-rank test showed that patients developing any type of cIRAE had longer progression-free survival than those without (p=0.023) and a better objective-response-rate (50% vs 18.5%, p=0.008).Conclusion: Most common cIRAEs in our study were pruritus and maculopapular rash. The incidence of cIRAEs was lower in our Indian cohort compared to that reported in Caucasian cohorts. Development of cutaneous immune-related adverse event in cancer patients on ICI was associated with a longer progression-free-survival and a better objective-response-rate. Thus, cIRAEs may serve as a surrogate marker for better patient outcomes.